2008
DOI: 10.1016/j.neuroimage.2007.09.045
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of functional development in normal infant brain using arterial spin labeled perfusion MRI

Abstract: Arterial spin labeled (ASL) perfusion MRI provides a noninvasive approach for longitudinal imaging of regional brain function in infants. In the present study, continuous ASL (CASL) perfusion MRI was carried out in normally developing 7-and 13-month old infants while asleep without sedation. The 13-month infant group showed an increase (P<0.05) of relative CBF in frontal regions as compared to the 7-month group using a region of interest based analysis. Using a machine-learning algorithm to automatically class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 45 publications
4
47
0
Order By: Relevance
“…After consumption of a flavanolrich cocoa drink, the 'flow oxygenation level dependent' (BOLD)-fMRI showed an increase in blood flow in certain regions of the brain, along with a modification of the BOLD response to task switching. Furthermore, 'arterial spin-labelling sequence magnetic resonance imaging' (ASL-MRI) [127] also indicated that cocoa flavanols increase CBF up to a maximum of two hours after ingestion of the flavanol-rich drink. In support of these findings, an increase in cerebral blood flow through the middle cerebral artery has been reported after the consumption of flavanol-rich cocoa using TCD [29].…”
Section: Cerebrovascular Effects Of Flavonoidsmentioning
confidence: 99%
“…After consumption of a flavanolrich cocoa drink, the 'flow oxygenation level dependent' (BOLD)-fMRI showed an increase in blood flow in certain regions of the brain, along with a modification of the BOLD response to task switching. Furthermore, 'arterial spin-labelling sequence magnetic resonance imaging' (ASL-MRI) [127] also indicated that cocoa flavanols increase CBF up to a maximum of two hours after ingestion of the flavanol-rich drink. In support of these findings, an increase in cerebral blood flow through the middle cerebral artery has been reported after the consumption of flavanol-rich cocoa using TCD [29].…”
Section: Cerebrovascular Effects Of Flavonoidsmentioning
confidence: 99%
“…Discussion ASL perfusion MR imaging was first described more than 10 years ago 20 and has been an active area of research. [21][22][23][24][25][26][27] ASL has several advantages compared with conventional bolustracking methods for migraine imaging. ASL requires no gadolinium-based contrast, can be repeated in the same session, and provides information on absolute CBF.…”
Section: Patientmentioning
confidence: 99%
“…Many other studies have looked at functional network development in young infants [19,20,22,56]. Fransson et al, in particular, examined the resting-state functional network architecture of very young preterm infants (25 weeks mean gestational age) and found that only half of the number of resting-state sub-networks found in healthy adults were present at the preterm stage [20].…”
Section: Introductionmentioning
confidence: 99%